2019
DOI: 10.1177/1043986219840231
|View full text |Cite
|
Sign up to set email alerts
|

Are the Deadliest Mass Shootings Preventable? An Assessment of Leakage, Information Reported to Law Enforcement, and Firearms Acquisition Prior to Attacks in the United States

Abstract: This study examined the 15 deadliest public mass shootings in the United States from March 1998 to February 2018 to assess (a) leakage of violent thoughts/intent, (b) leakage of specific interest in mass killing, (c) concerning behaviors reported to law enforcement, (d) concerning interest in homicide reported to law enforcement, and (e) firearms acquisition. We then compared our findings on the deadliest public mass shooters with the Federal Bureau of Investigation’s (FBI) findings on active shooters in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 33 publications
0
47
1
Order By: Relevance
“…In many ideologically motivated homicides, perpetrators in the Internet age have posted manifestos online prior to the commission of the offense. This was the case in the lone-actor terrorist killings in Oslo and Utøya, Norway, in 2011; the Isla Vista, CA rampage in 2014; the Charleston, SC, church shooting in 2015; the 2019 shootings in Christchurch, New Zealand, and El Paso, TX; and the murder of a federal judge's son by a misogynistic attorney in 2020, to name only a few (Arango et al, 2019;Barnes, 2012;Hamm & Ayers, 2021;Hong et al, 2020;Lankford, 2018;Lankford et al, 2019;Liem & Geelen, 2019;Tully, 2020;White, 2017). These manifestos may take the form of a written letter or essay, social media postings, or videos recorded and uploaded prior to the offense.…”
Section: Self-publishing and Media Sharingmentioning
confidence: 99%
“…In many ideologically motivated homicides, perpetrators in the Internet age have posted manifestos online prior to the commission of the offense. This was the case in the lone-actor terrorist killings in Oslo and Utøya, Norway, in 2011; the Isla Vista, CA rampage in 2014; the Charleston, SC, church shooting in 2015; the 2019 shootings in Christchurch, New Zealand, and El Paso, TX; and the murder of a federal judge's son by a misogynistic attorney in 2020, to name only a few (Arango et al, 2019;Barnes, 2012;Hamm & Ayers, 2021;Hong et al, 2020;Lankford, 2018;Lankford et al, 2019;Liem & Geelen, 2019;Tully, 2020;White, 2017). These manifestos may take the form of a written letter or essay, social media postings, or videos recorded and uploaded prior to the offense.…”
Section: Self-publishing and Media Sharingmentioning
confidence: 99%
“…In addition to policies designed to reduce the number of people who want to kill large numbers of victims, some policies could help counteract potential public mass shooters’ methods. In particular, although it may be impossible to keep these offenders from engaging in long planning periods or developing extensive attack strategies, we may be able to reduce their access to firearms, which would represent important progress because most active and public mass shooters have obtained their weapons legally (Lankford, Adkins, & Madfis, ; Silver et al., ).…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…The key would be to exploit some of the factors that make the deadliest attackers different from other perpetrators. Researchers have shown that compared with less lethal offenders, the deadliest perpetrators seem much more likely to (a) plan their attacks for more than 1 year, (b) reveal their violent thoughts/intent prior to attacking, (c) reveal their specific interest in mass killing, (d) be reported to law enforcement for their concerning behavior, and (e) be reported to law enforcement for their concerning interest in homicide (Lankford et al., ).…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…A minuscule percentage of people fitting this demographic carry out this rare form of violence. For instance, Lankford et al (2019) claim that the per capita likelihood of a person carrying out a mass shooting in the United States is less than one in a million. Likewise, only one in two million school youth die from homicide or suicide at school each year (Muschert, 2007, p. 61).…”
mentioning
confidence: 99%